THE LIFE AND CAREER SKILLS AMONG TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING (TVET) STUDENTS - Abdullah, Nurhanim Saadah; Sumarwati, Sri; Aziz , Mohd Ismail Abd; Ziden, Azidah Abu; Jalil, Siti Afiat (International Journal of Psychosocial Rehabilitation, 2020)
Unemployment is one of the problems faced in many countries. A gap between the skills required by employers and possessed by graduates is one of the factors of unemployment. In such situations, it is important to investigate whether life and career skills are being embedded by higher education institutions, especially in technical and vocational education since it provides a semi-skilled and skilled workforce to compete in the global labor market. This study was conducted to investigate the differences between life and career skills among technical and vocational education and training (TVET) students in different departments in Malaysia. The quantitative research involves TVET students who enrolled in diploma programs at polytechnics in Malaysia. There were five departments involved in this study, namely the Electrical Engineering Department (EE), the Mechanical Engineering Department (ME), the Civil Engineering Department (CE), the Department of Commerce (COMM) and the Tourism and Hospitality Department (TH). A total sample of 821 diploma students from three types of polytechnics (Premier, Conventional and METrO) was selected using a disproportionate sampling method. Data was collected using a questionnaire with Likert Scale 5, consisting of 80 items. The collected data were analyzed using the Statistical Package for the Social Science (SPSS) program version 21 with an analysis of variance (ANOVA) used as statistical analysis. The finding suggested that students in the five different departments possessed no difference in productivity and accountability skills, and responsibility and leadership skills. Meanwhile, students from the five different departments have similarities in terms of initiative, self-direction, social and cross-cultural skills. Different departments have their ways of embedding their teaching and learning process towards their students. This study may be used to promote and assist in higher education, specifically polytechnics and industries to improve and enhance TVET programs. The students should be provided with training and skills to survive in the real working environment.